2011
DOI: 10.1016/j.ijantimicag.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of resistance to macrolides, lincosamides and streptogramins in Staphylococcus saprophyticus clinical isolates

Abstract: The aim of this study was to evaluate the prevalence of resistance to macrolide-lincosamide-streptogramin (MLS) antibiotics as well as to assess the molecular basis of this resistance amongst 72 Staphylococcus saprophyticus urinary isolates collected from 2005 to 2009 in University Hospital of Caen (France). Of the 72 strains studied, 33 (45.8%) were resistant to at least one MLS antibiotic, including 24 (72.7%) with an M phenotype, 5 (15.2%) with an inducible MLS(B) phenotype, 3 (9.1%) with a combined M+L phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
1
21
1
2
Order By: Relevance
“…Macrolide resistance in MRSA is significantly higher than in methicillin-susceptible S. aureus (MSSA) and, in a recent study in Turkey, there was a sevenfold difference in macrolide resistance between MRSA and MSSA (Gul et al 2008;Yildiz et al 2014;Aydeniz Ozansoy et al 2015). The rates of macrolide resistance in coagulase-negative staphylococci vary from 44% (Staphylococcus saprophyticus, France, Le Bouter et al 2011) to 100% (S. haemolyticus, Poland, Brzychczy-Wloch et al 2013S. hominis, Poland, Szczuka et al 2015) in surveillance studies (Table 2).…”
Section: Surveillance Of Macrolide Resistance and Characterization Ofmentioning
confidence: 99%
“…Macrolide resistance in MRSA is significantly higher than in methicillin-susceptible S. aureus (MSSA) and, in a recent study in Turkey, there was a sevenfold difference in macrolide resistance between MRSA and MSSA (Gul et al 2008;Yildiz et al 2014;Aydeniz Ozansoy et al 2015). The rates of macrolide resistance in coagulase-negative staphylococci vary from 44% (Staphylococcus saprophyticus, France, Le Bouter et al 2011) to 100% (S. haemolyticus, Poland, Brzychczy-Wloch et al 2013S. hominis, Poland, Szczuka et al 2015) in surveillance studies (Table 2).…”
Section: Surveillance Of Macrolide Resistance and Characterization Ofmentioning
confidence: 99%
“…genes, PCR assays were performed as described by Geha et al (1994), Ardic et al (2006) and Le Bouter et al (2011).…”
Section: Detection Of Antibiotic Resistance Genes For the Detection mentioning
confidence: 99%
“…The mecA gene that encodes an alternative binding protein with decreased binding affinity to meticillin, and others for beta-lactam antibiotics, are part of a mobile genetic element called the staphylococcal chromosome mec (SCCmec). The genes code for methylases, erm(A)and erm (B), that modify the target site in 23S rRNA and thereby inhibit the binding of macrolide-lincosamide streptogramin B (MLS B ) antibiotics, and are associated with transposons Tn554 and Tn917/ Tn551, while the erm(C) gene was identified on small plasmids (Le Bouter et al, 2011). The lnu(A) gene encodes a lincosamide nucleotidyltransferase, which confers resistance to lincosamides and is located on small plasmids.…”
Section: Introductionmentioning
confidence: 99%
“…While S. sciuri and sal(A) cannot be seen as immediate threats to public health, both should be included in the monitoring memos for MLS antibiotic resistance surveys. In addition, the report of the presence of a sal(A)-related pseudogene in S. saprophyticus might be of epidemiological concern, especially since none of the thus-far-described resistance genes can be found in an ML-resistant strain (36). Indeed, it was recently reported that only one nucleotide mutation within a resident cryptic AREencoding gene of the Enterococcus faecium genome would be enough to generate an LS A -resistant strain from a susceptible one (37).…”
Section: Figmentioning
confidence: 99%